Comparison of Effectiveness of Peroral Endoscopic Myotomy-Transoral Incisionless Fundoplication (POEM-TIF) Compared with Laparoscopic Heller Myotomy (LHM) in the Management of Achalasia - Qadri, Annisa Salsabila; Zahroni, Siti; Naradhea, Gede; Maurae, Perlin Nigel Valencia; Yolanda, Rizky; Mahasuary, Shaffany; Nabila, Aqilla Nasywa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Achalasia is a condition characterized by the absence of lower esophageal peristalsis and the lower esophageal sphincter, resulting in incomplete relaxation and swallowing difficulties. This literature review aims to identify POEM-TIF as a modified technique that can be directly compared with LHM, currently considered the gold standard, to evaluate long-term effectiveness, safety, and quality of life in postoperative patients. The article was compiled using a literature review method. The literature used was selected based on inclusion criteria, namely articles relevant to achalasia, Peroral Endoscopic Myotomy (POEM), and Laparoscopic Heller Myotomy (LHM). The literature review found that achalasia is a rare condition with a global prevalence ranging from 1.8 to 12.6 per 100,000 people per year. As understanding of the pathophysiology of achalasia increases, various treatment options have evolved. The latest technique, Peroral Endoscopic Myotomy (POEM), offers the advantage of being less invasive and having a higher success rate for type III achalasia compared to LHM. However, POEM has the same drawbacks, namely a higher incidence of postoperative GERD compared to LHM. This latest research developed a modification of POEM therapy known as POEM-TIF, a combination of POEM and Transoral Incisionless Fundoplication (TIF). The addition of Transoral Incisionless Fundoplication (TIF) as an additional procedure can help reduce reflux symptoms and improve patients' quality of life by creating a more effective barrier between the stomach and esophagus. Understanding the advantages and disadvantages of LHM compared to POEM-TIF, which has anti-reflux properties, is crucial for in-depth study considering the impact of achalasia on quality of life.